Financial fragility of euro area households - Miguel Ampudia; Has van Vlokhoven; Dawid Żochowski (European Central Bank (ECB), 2014)
We propose a novel framework to identify distressed households by taking account of both the solvency and the liquidity situation of an individual household. Using the data from the Household Finance and Consumption Survey and the country-level data on non-performing loans we calibrate our metric of distress and estimate stress-test elasticities in response to an interest rate shock, an income shock and a house price shock. We find that, albeit euro area households are relatively resilient as a whole, there are large discrepancies in the impact of macroeconomic shocks across countries. Furthermore, while losses given default as calculated using our framework are low, they are sensitive to house prices changes. Hence, any factors hindering the seizure of the collateral or lowering its value, such as inefficient legal systems, moratoria on foreclosures or bottlenecks in judicial procedures may significantly increase losses facing banks. Finally, we demonstrate that our framework could be used for macroprudential purposes, in particular for the calibration of country level loan-to-value ratio caps.
Keywords: D10; D14; G21; 330; financial stability; household finance; household indebtedness; stress testing